2016
DOI: 10.1080/14397595.2016.1179861
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormally increased low-density granulocytes in peripheral blood mononuclear cells are associated with interstitial lung disease in dermatomyositis

Abstract: The abnormal increase of LDGs may exacerbate abnormal NET regulation and further contribute to the pathogenesis of ILD in DM patients by abnormally forming NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
2
23
0
3
Order By: Relevance
“…This probably happens because it suppresses the immune response allowing mycobacterium growth. In severe asthma [15] and in interstitial lung disease in dermatomyositis [16], similar to what was described in autoimmune diseases like SLE and RA, the LDG acts worsening the pathologic condition.…”
Section: Neutrophil Subtypes Generated In Specific Conditionssupporting
confidence: 53%
“…This probably happens because it suppresses the immune response allowing mycobacterium growth. In severe asthma [15] and in interstitial lung disease in dermatomyositis [16], similar to what was described in autoimmune diseases like SLE and RA, the LDG acts worsening the pathologic condition.…”
Section: Neutrophil Subtypes Generated In Specific Conditionssupporting
confidence: 53%
“…Recent evidence shows that neutrophils are actively involved in both innate and adaptive immunity, and play an important pathogenetic role in many autoimmune diseases. Although the role of neutrophils in IIM has not been deeply investigated, patients with PM/DM have an increased number of low density granulocytes (LDCs), a proinflammatory subtype of human neutrophils, in peripheral blood [ 47 ]. In addition, patients with PM/DM-associated ILD have significantly an enhanced formation of neutrophil extracellular traps, and the decreased degradation of neutrophil extracellular traps can directly prime T cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported a higher percentage of low-density granulocytes (LDGs) along with enhanced NET-formation capabilities in patients with DM as compared with healthy controls, and that this percentage was also higher in DM patients with ILD than in those without. Additionally, LDG percentage was positively correlated with lung disease activity scores [ 30 ]. In line with these reports, the present results showed that increased HNP levels in the plasma and BALF from patients with myositis-associated ILD suggested that neutrophils are likely to release NETs, including HNPs, which are difficult to degrade in patients with myositis-associated ILD.…”
Section: Discussionmentioning
confidence: 99%